Periodontal surgery as treatment of periodontitis stage 1 grade A: Bedah periodontal sebagai tatalaksana periodontitis stage 1 grade A - Qonitah Nur Aslamiyah; Farah Fathia Fauzia; M. Rijal Dermawan K; Steffi Triany Arnov (Makassar Dental Journal PDGI Makassar, 2026)
Periodontitis is an inflammatory disease of the periodontal tissues caused by certain microorganisms and characterised by the loss of periodontal tissue. Ac-cording to the American Academy of Periodontology in 2018. Periodontitis is classified into four stages based on the severity of the disease and the complex-ity of treatment, and three grades based on its progression. A 20-year-old woman presented to the Periodontology Department of RSGMP Unimus in Septem-ber 2024 with complaints of swollen gums and frequent bleeding during toothbrushing. Based on the medical history, clinical examination, and supporting tests, the patient was diagnosed with stage 1 grade A periodontitis accompanied by gingival enlargement. It was concluded that periodontal surgery showed a good success rate, resulting in the gingiva no longer being enlarged, having a coral pink colour, a firm consistency, stippling, and sharp interdental papillae.